Low utilization of confirmatory testing for tinea capitis by pediatricians at an academic center in New York, United States, 2005–2021 - Hwang, Jonathan K.; Gold, Jeremy A. W.; Paller, Amy S.; Lipner, Shari R. (Frontiers in Pediatrics, 2023)
We retrospectively reviewed physician diagnostic and treatment practices for pediatric tinea capitis at an academic institution over 16 years, in assessing adherence with published guidelines. We demonstrate the need to increase utilization of confirmatory testing and systemic therapy, and call for directed pediatrician education towards these goals.